BEYOND REALITY: Head-Mounted Displays for Mobile Systems Researchers - Cuervo, Eduardo (GetMobile, 2017)
Head-Mounted Displays (HMDs) have finally reached the point where they can comfortably and affordably transport people to virtual worlds or transform their physical reality by feeding timely information straight to their eyes. However, the technology behind HMDs is still not fully mature. There are plenty of open challenges in wireless networking, cloud computing, security, and privacy, as well as opportunities to create novel applications.